Facial diplegia with hyperreflexia-a mild Guillain-Barre Syndrome variant, to treat or not to treat? - Sethi, Nitin K; Torgovnick, Josh; Arsura, Edward; Johnston, Alissa; Buescher, Elizabeth (Journal of Brachial Plexus and Peripheral Nerve Injury, 2007)
Guillain Barre Syndrome (GBS) is readily diagnosed when the presentation is that of ascending weakness and areflexia. Atypical presentations with preserved, and at times, brisk reflexes, can be a diagnostic dilemma. We describe a patient with GBS who presented with facial diplegia and hyperreflexia on examination and discuss management options.